α4-Containing GABAA Receptors are Required for Antagonism of Ethanol-Induced Motor Incoordination and Hypnosis by the Imidazobenzodiazepine Ro15-4513 - Iyer, Sangeetha V.; Benavides, Rodrigo; Chandra, Dev; Cook, James M.; Rallapalli, Sundari; June, Harry L.; Homanics, Gregg E. (Frontiers in Pharmacology, 2011)
Alcohol (ethanol) is widely consumed for its desirable effects but unfortunately has strong addiction potential. Some imidazobenzodiazepines such as Ro15-4513 are able to antagonize many ethanol-induced behaviors. Controversial biochemical and pharmacological evidence suggest that the effects of these ethanol antagonists and ethanol are mediated specifically via overlapping binding sites on α4/δ-containing GABAA-Rs. To investigate the requirement of α4-containing GABAA-Rs in the mechanism of action of Ro15-4513 on behavior, wildtype (WT) and α4 knockout (KO) mice were compared for antagonism of ethanol-induced motor incoordination and hypnosis. Motor effects of ethanol were tested in two different fixed speed rotarod assays. In the first experiment, mice were injected with 2.0 g/kg ethanol followed 5 min later by 10 mg/kg Ro15-4513 (or vehicle) and tested on a rotarod at 8 rpm. In the second experiment, mice received a single injection of 1.5 g/kg ethanol +/- 3 mg/kg Ro15-4513 and were tested on a rotarod at 12 rpm. In both experiments, the robust Ro15-4513 antagonism of ethanol-induced motor ataxia that was observed in WT mice was absent in KO mice. A loss of righting reflex (LORR) assay was used to test Ro15-4513 (20 mg/kg) antagonism of ethanol (3.5 g/kg)-induced hypnosis. An effect of sex was observed on the LORR assay, so males and females were analyzed separately. In male mice, Ro15-4513 markedly reduced ethanol-induced LORR in WT controls, but α4 KO mice were insensitive to this effect of Ro15-4513. In contrast, female KO mice did not differ from WT controls in the antagonistic effects of Ro15-4513 on ethanol-induced LORR. We conclude that Ro15-4513 requires α4-containing receptors for antagonism of ethanol-induced LORR (in males) and motor ataxia.